3ds max design architectural visualization for intermediate users - Smith, Brian L. 1972- (Focal Press, 2012)
Learn time-saving techniques and tested production-ready tips for maximum speed and efficiency in creating professional-level architectural visualizations in 3ds Max. Move from intermediate to an advanced level with specific and comprehensive instruction with this collaboration from nine different authors from around the world. Get their experience and skills in this full-color book, which not only teaches more advanced features, but also demonstrates the practical applications of those features to get readers ready for a real production environment. Fully updated for the most recent version of 3ds Max. * How to read, clean, and prepare architectural drawings for use in 3ds Max * How to build efficient 2D and 3D sites, as well as the structures placed on them * How to manage an animation project from start to finish * The essentials of the ever-improving mental ray render engine * Production tips, marketing strategies, and business tools.
Print version record
Keywords: 3ds max (Computer file); Computer animation; Architecture -- Computer-aided design; Architectural rendering -- Computer simulation; Three-dimensional display systems; Computer graphics; Computer Graphics; Animation par ordinateur; Rendu d'architecture; Simulation par ordinateur; Affichage tridimensionnel; Infographie; Architecture; Conception assistée par ordinateur; computer animation; three-dimensional; computer graphics; COMPUTERS; Digital Media; Video & Animation